Nongovernmental organizations and postprison life: examining the role of religion - Kaufman, Nicole (Punishment & society, 2019)
This article examines the relevance of religion for nongovernmental organizations that work with formerly incarcerated people. Despite the increased visibility of religious nongovernmental organizations working with criminalized people, research on the nongovernmental sector and criminal justice still largely focuses on secular organizations. This article argues for the conceptual importance of religion and its role shaping work in this sector, and draws from the sociology of religion to theorize the importance of discourses and practices in organizational settings. I present a typology identifying nongovernmental organizations’ religious approaches, which I developed using archival, interview, and observational data from 18 nongovernmental organizations in Wisconsin. I differentiate among nongovernmental organizations that I call secular, which stay away from religion, religiously inspired, which operate based on religious principles, and reciprocally religious, which hold expectations of religious practices from program participants. Moving beyond single-case studies enables a comparative analysis of the ideas and practices among actors that serve and seek to shape people leaving prison, whose work varies in terms of predominant denominations, assumptions about morality and sin, and relationships with churches and the medical profession. The results encourage further inquiry into what religious nongovernmental organizations do, why, and how, given the distinctive discursive and material resources and practices that they bring into work with criminalized people.